Sosialisasi Stunting Sebagai Upaya Pencegahan Stunting Di Desa Aikmel Utara, Kabupaten Lombok Timur - Agustina Dwi Lestari; Huraiza Mahmudah (Postgraduate Program, University of Mataram, 2025)
Stunting is a serious health issue that remains a significant challenge in Indonesia, including in Aikmel Utara Village, East Lombok Regency. This problem is caused by chronic malnutrition, repeated infections, and improper parenting, which negatively affect children's physical and cognitive development. The stunting socialization program carried out by KKN PMD Universitas Mataram aims to raise community awareness about the importance of balanced nutrition and healthy lifestyles to prevent stunting. Survey results show that 90% of stunting cases in Aikmel Utara Village are caused by inadequate dietary and parenting practices, despite the parents' sufficient financial conditions. In this socialization event, speakers from Universitas Mataram and STIKES Graha Edukasi Makassar explained the importance of sensitive interventions from parents and provided recommendations to strengthen the role of posyandu cadres and educate the community. In addition to the socialization, KKN students also distributed Supplementary Feeding Packages (PMT) to mothers of stunted children to help improve family nutrition. It is hoped that through a community-based approach and community empowerment, the stunting issue in Aikmel Utara Village can be effectively and sustainably addressed. Keywords: Stunting, socialization, balanced nutrition, parenting, Aikmel Utara Village